THE IMPACT OF THE TRADITIONAL GAME OF HIDE AND SEEK (MA'TINGKO-TINGKO) FOR IMPROVING CHILDREN'S SOCIAL SKILLS IN MADELLO VILLAGE, BALUSU DISTRICT, BARRU REGENCY - Yuniar Yuniar (UNM Geographic Journal, 2022)
This study aims to describe the traditional game of hide and seek (ma'tingko-tingko) and to determine the impact of the traditional game of hide and seek (ma'tingko-tingko) for improving children's social skills in Madello Village, Balusu District, Barru Regency. The type of research used in this research is descriptive qualitative research method. The data collection techniques through natural observation, interviews and documentation. The data collection process carried out by researchers includes data collection, data reduction, data presentation and drawing conclusions. The results obtained are that (1) The description of the traditional game of hide and seek (ma'tingko-tingko) in Madello Village, Balusu District, Barru Regency is one of the fun games and is favored by the community, especially among children in Madello Village, Balusu District. (2) The impact of the traditional game of hide and seek (ma'tingko-tingko) for improving children's social skills in Madello Village, Balusu District, Barru Regency, is to have a positive impact on improving children's social skills.